Nanostructure, thermoelectric properties, and transport theory of V2VI3 and V2VI3/IV–VI based superlattices and nanomaterials. Issue 3 (7th January 2016) - Dankwort, Torben; Hansen, Anna‐Lena; Winkler, Markus; Schürmann, Ulrich; Koenig, Jan D.; Johnson, David C.; Hinsche, Nicki F.; Zahn, Peter; Mertig, Ingrid; Bensch, Wolfgang; Kienle, Lorenz
Abstract : The scope of this work is to review the thermoelectric properties, the microstructures, and their correlation with theoretical calculations and predictions for recent chalcogenide based materials. The main focus is put on thin multilayered Bi2 Te3, Sb2 Te3 films, and bulk V2 VI3 /IV–VI mixed systems. For all films a systematic characterization of the thermoelectric properties as well as the micro‐ and nanostructure was performed. The degree of crystallinity of the multilayered films varied from epitaxial systems to polycrystalline films. Other multilayered thin films revealed promising thermoelectric properties. (SnSe)1.2 TiSe2 thin films with rotational disorder yielded the highest Seebeck coefficient published to date for analogous materials. For bulk V2 VI3 /IV–VI mixed systems insides are given into a complete "material to module" process resulting in a high performance thermoelectric generator using (1 –x )(GeTe) x (Bi2 Se0.2 Te2.8 ) ( x  = 0.038). Cyclic heating of this system with x  = 0.063 resulted in a drastic change of the micro‐ and nanostructure observed by ex situ and in situ X‐ray diffraction (XRD) and transmission electron microscopy (TEM). Consequently a degradation of ZT at 450 °C from ∼2.0 to ∼1.0 was observed, while samples with x  = 0.038 showed a stable ZT of 1.5. Abstract : The scope of this work is to review the thermoelectric properties, the microstructure, and their correlation with theoretical calculations and predictions for recent chalcogenide based materials. The main focus of this Feature Article is put on thin multilayer films and bulk V2 VI3 /IV–VI mixed systems.